Forest Fire , Haze Pollution and Climate Change - Srivastava, Rajiv K.; Singh, Dhan (Indian Forester, 2003)
Forest ecosystems are influenced by a variety of factors , both natural and human induced , which ultimately led to change in biodiversity and consequently changes the climate of existing system. Climate warming due to anti-environmental human activities has resulted a threat to biodiversity. Forest fire is one of the major factors , which influence the forest ecosystem and climate of the entire region. One factor may not solely responsible for any change in climate. This is a complex system in which biota; plants in particular , interact with climate and with atmospheric gases. Forests play an important role in sequestration of carbon globally. The study of impact of forest fire on existing forest ecosystem is inevitably required for the further mitigation to the problem. The present paper examines the impact of forest fire on climate change and forest biodiversity.